Income distribution in macroeconomic models - Bertola, Giuseppe; Foellmi, Reto; Zweimüller, Josef (Princeton (New Jersey) Princeton University Press, 2014)
This book looks at the distribution of income and wealth and the effects that this has on the macroeconomy, and vice versa. Is a more equal distribution of income beneficial or harmful for macroeconomic growth, and how does the distribution of wealth evolve in a market economy? Taking stock of results and methods developed in the context of the 1990s revival of growth theory, the authors focus on capital accumulation and long-run growth. They show how rigorous, optimization-based technical tools can be applied, beyond the representative-agent framework of analysis, to account for realistic
Keywords: Ingresos -- Distribución -- Modelos econométricos; Economía del bienestar -- Modelos econométricos; Desarrollo económico -- Modelos econométricos